2010
DOI: 10.2478/s11535-010-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of red raspberry (Rubus idaeus L.) populations in Lithuania

Abstract: Abstract:The red raspberry (Rubus idaeus L.) is widely distributed in Lithuania and occupies a range of habitats. The presence of coadapted gene pools in local populations of R. idaeus is a question of interest not only to plant scientists, but also to plant breeders. In this study, we investigated the genetic structure of R. idaeus and the influence of local habitats on the genetic diversity within and among populations. Nineteen populations of R. idaeus were sampled from different habitats in various agrocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Despite the rather small territory of Lithuania, the ecological-climatological conditions in the eastwest and south-north direction are rather different [44], and climate warming may be the one of reasons for the spread of E. annuus in the northern direction. Small but significant differences (8% for RAPD markers; 5% for ISSR markers) between molecular variance found among the three regions considered in our work ( Table 5) and high population genetic structuring (Φ PR =0.49 for RAPD markers; Φ PR =0.58 for ISSR markers) can be explained in several ways, including the multiple founders and possible habitat-genotype interaction [30,45,46]. Trtikova et al [17] also identified a high level of genetic differentiation among populations from Switzerland.…”
Section: Discussionmentioning
confidence: 58%
“…Despite the rather small territory of Lithuania, the ecological-climatological conditions in the eastwest and south-north direction are rather different [44], and climate warming may be the one of reasons for the spread of E. annuus in the northern direction. Small but significant differences (8% for RAPD markers; 5% for ISSR markers) between molecular variance found among the three regions considered in our work ( Table 5) and high population genetic structuring (Φ PR =0.49 for RAPD markers; Φ PR =0.58 for ISSR markers) can be explained in several ways, including the multiple founders and possible habitat-genotype interaction [30,45,46]. Trtikova et al [17] also identified a high level of genetic differentiation among populations from Switzerland.…”
Section: Discussionmentioning
confidence: 58%
“…Geographically, the Kamchatka (Russia) populations (RU1, RU2, and RU3) are closer to the JP population than populations from the Baltic region. This discrepancy could be the result of adaptation to local environmental conditions [ 44 , 53 , 54 ]. For example, Kamchatka populations experience a more severe climate with colder winters and shorter summers than the other studied populations.…”
Section: Discussionmentioning
confidence: 99%
“…This can pose problems in the future since the material is quite homogeneous, which can lead to both production and breeding problems, due to the lack of diversity of novel valuable breeding characteristics. Therefore, new, genetically differentiated germplasm should be introduced and/or the use of wild relatives should be promoted (Patamsytë et al, 2010) to continue successful breeding efforts. This finding supports previous reports about the very limited genetic diversity in raspberry breeding programmes and the necessity to introduce new germplasm (Dale et al, 1993).…”
Section: Discussionmentioning
confidence: 99%